Antioxidant and Anti-Inflammatory Effects of Genus Gynura: A Systematic Review - Tan, Jiah Ning; Mohd Saffian, Shamin; Buang, Fhataheya; Jubri, Zakiah; Jantan, Ibrahim; Husain, Khairana; Mohd Fauzi, Norsyahida (Frontiers in Pharmacology, 2020)
Background: Gynura species have been used traditionally to treat various ailments, such as fever, pain, and to control blood glucose level. This systematic review critically discusses studies regarding Gynura species that exhibited antioxidant and anti-inflammatory effects, thus providing perspectives and instructions for future research of the plants as a potential source of new dietary supplements or medicinal agents. Methods: A literature search from internet databases of PubMed, Scopus, Science Direct, EThOS, and ProQuest was carried out using a combination of keywords such as “Gynura,” “antioxidant,” “anti-inflammatory,” or other related words. Research articles were included in this study if they were experimental (in vitro and in vivo) or clinical studies on the antioxidant or anti-inflammatory effects of Gynura species and if they were articles published in English. Results: Altogether, 27 studies on antioxidant and anti-inflammatory effects of Gynura species were selected. The antioxidant effects of Gynura species were manifested by inhibition of ROS production and lipid peroxidation, modulation of glutathione-related parameters, and enzymatic antioxidant production or activities. The anti-inflammatory effects of Gynura species were through the modulation of inflammatory cytokine production, inhibition of prostaglandin E2, nitric oxide, cellular inflammation, and inflammation in animal model. The potential anti-inflammatory signaling pathways modulated by Gynura species are GSK3, Nrf2, PPARγ, MAPK, NF-κB, and PI3K/Akt. However, most reports on antioxidant and anti-inflammatory effects of the plants were on crude extracts, and the chemical constituents contributing to bioactivities were not clearly understood. There is a variation in quality of studies in terms of design, conduct, and interpretation, and in-depth studies on the underlying mechanisms involved in antioxidant and anti-inflammatory effects of the plants are in demand. Moreover, there is limited clinical study on antioxidant and anti-inflammatory effects of Gynura species. Conclusion: This review highlighted antioxidant and anti-inflammatory effects of genus Gynura and supported their traditional uses to treat oxidative stress and inflammatory-related diseases. This review is expected to catalyze further studies on genus Gynura. However, extensive preclinical data need to be generated from toxicity and pharmacokinetic studies before clinical studies can be pursued for their development into clinical medicines to treat oxidative stress and inflammatory conditions.